2010
DOI: 10.1387/ijdb.103139dk
|View full text |Cite
|
Sign up to set email alerts
|

The expression of teneurin-4 in the avian embryo: potential roles in patterning of the limb and nervous system

Abstract: Teneurins are type II transmembrane proteins that play important roles in pattern formation in Drosophila, axon fasciculation and organogenesis in Caenorhabidits elegans, and neuronal pathfinding in the visual system of the mouse. There is evidence that a peptide derived from a proteolytic event near the C-terminus of teneurins leads to formation of an active neuropeptide, while processing at and near the transmembrane domain leads to shedding of the extracellular domain into the extracellular matrix and the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…In different cell lines, siRNAs reduced Ten-2 and Ten-4 mRNA levels by 80–85% and by 70–90%, respectively, which however did not cause consistent effects on the expression of BCL2, BIRC5, CASP3, and CASP8 (S9 Fig). Similarly, VEGF mRNA levels were not significantly altered, although a potential role of Ten-4 in angiogenesis was previously suggested based on its immunolocalization in coronary and tumor blood vessels [45,46]. In contrast, we consistently measured a ∼20% increase in proliferation at 72 h in MCF7 and BT474 cells treated with Ten-4-specific siRNA, with the latter achieving significance (P = .0024, parametric comparison of independent means) (Fig 8A).…”
Section: Resultssupporting
confidence: 61%
“…In different cell lines, siRNAs reduced Ten-2 and Ten-4 mRNA levels by 80–85% and by 70–90%, respectively, which however did not cause consistent effects on the expression of BCL2, BIRC5, CASP3, and CASP8 (S9 Fig). Similarly, VEGF mRNA levels were not significantly altered, although a potential role of Ten-4 in angiogenesis was previously suggested based on its immunolocalization in coronary and tumor blood vessels [45,46]. In contrast, we consistently measured a ∼20% increase in proliferation at 72 h in MCF7 and BT474 cells treated with Ten-4-specific siRNA, with the latter achieving significance (P = .0024, parametric comparison of independent means) (Fig 8A).…”
Section: Resultssupporting
confidence: 61%
“…Previous studies in mice showed that Teneurin-3 regulates the development of topography in the retinogeniculate (Leamey et al., 2007) and retinocollicular pathways (Dharmaratne et al., 2012), specifically for the ipsilaterally projecting RGC population. However, the fact that teneurin-3 is not exclusively expressed in ipsilaterally projecting RGCs (Leamey et al., 2007) and is also found in the visual system of species where RGCs project contralaterally only, like chick (Kenzelmann-Broz et al., 2010) and zebrafish (Mieda et al., 1999; this study), clearly suggests additional functions in vertebrate visual system development.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, oligodendrocytes are electrically active as well (Káradóttir et al, 2008) and their membrane potential can influence conduction velocity (Yamazaki et al, 2007). Recently, Teneurin-4 has been identified as a regulator of oligodendrocyte differentiation and myelination (Suzuki et al, 2012) and, as it is expressed in the auditory brainstem, it might play a role in functional myelination (Kenzelmann-Broz et al, 2010). …”
Section: Mechanisms Of Internode Distance Regulationmentioning
confidence: 99%